The UDHR and Confucian Community: A Case of Confucian Religious Education Erasure in Indonesia - Lemuel Christandi, Yohanes Babtista (Diponegoro University, 2024)
The Universal Declaration of Human Rights (UDHR) and Confucianism have a complex relationship in Indonesia. Therefore, this article focuses on the relationship between human rights principles and religious traditions that consider the importance of the UDHR for Confucians. It is also related to the fulfilment of the rights to freedom of religion and education, and it focuses on the case of the elimination of Confucian religious education during the New Order in Indonesia. This article is compiled using historical methods. The primary sources used are Supreme Council of the Confucian Religion (MATAKIN) correspondence with the government officials. The study results show that the Confucian community uses the UDHR as a promotional medium for Confucian religious education in schools. In addition, they fight for Confucianism to gain legal recognition as a religion.